A pixelated liquid perovskite array for high-sensitivity and high-resolution X-ray imaging scintillation screens - Hu, Mingzhu (2024)
Scintillators with high spatial resolution at a low radiation dose rate are desirable for X-ray medical imaging. A low radiation dose rate can be achieved using a sufficiently thick scintillator layer to absorb the incident X-ray energy completely, however, often at the expense of low spatial resolution due to the issue of optical crosstalk of scintillation light. Therefore, to achieve high sensitivity combined with high-resolution imaging, a thick scintillator with perfect light guiding properties is in high demand. Herein, a new strategy is developed to address this issue by embedding liquid scintillators into lead-containing fiber-optical plates (FOPs, n = 1.5) via the siphon effect. The liquid scintillator is composed of perovskite quantum dots (QDs)/2,5-diphenyloxazole (PPO) and the non-polar high-refractive index (n = 1.66) solvent α-bremnaphthalene. Benefiting from the pixelated and thickness-adjustable scintillators, the proposed CsPbBr3 QDs/PPO liquid scintillator-based X-ray detector achieves a detection limit of 79.1 μGy s-1 and a spatial resolution of 4.6 lp mm-1. In addition, it displays excellent tolerance against radiation (>34 h) and shows outstanding stability under ambient conditions (>160 h). This strategy could also be applied to other liquid scintillators (such as CsPbCl3 QDs and Mn:CsPbCl3 QDs). The combination of high sensitivity, high spatial resolution and stability, easy fabrication and maintenance, and a reusable substrate matrix makes these liquid scintillators a promising candidate for practical X-ray medical imaging applications.